PEMBUATAN TEH FUNGSIONAL BERBAHAN DASAR BUAH MAHKOTA DEWA (Phaleria macrocarpa) DENGAN PENAMBAHAN DAUN STEVIA - Amriani, Herviana; Syam, Husain; Wijaya, Mohammad (Universitas Negeri Makassar, 2019)
The aim of this study was to determine the effect of adding stevia leaves to the production of the crown god fruit tea produced and to find out the reception of the panelists on the produced crown god fruit tea. This study used a one-factor completely randomized design (CRD) method with 6 levels of treatment (Fruit crown god: Stevia leaves), namely 5: 1, 5: 2, 5: 3, 5: 4, 5: 5. The first stage is the red crown of the fruit which is sorted and then washed thoroughly. The second stage of the flesh of the god's crown is then thinly sliced and then dried. The third stage is added dry stevia leaves with various concentrations namely 1 g, 2 g, 3 g, 4 g, and 5 g. The last stage is the dried crown god fruit that has been added to the stevia leaf, brewed with 200 ml of hot water, then stirred evenly. The parameters observed were the antioxidant, polyphenol, and sugar levels. The data analysis technique used in this study was variance analysis which was then processed using SPSS version 22. The results showed that the treatment of adding stevia leaves to the antioxidant, polyphenol and total sugar levels in the treatment of the crown god fruit: Stevia leaves (5: 5) is the best treatment with an antioxidant value of 90.73%, polyphenols 0.6128 mg / ml, and total sugar content of 1.42%.